ANALISIS DETERMINAN BELANJA MODAL PEMERINTAH DAERAH KABUPATEN/KOTA DI JAWA TENGAH - Yuni Puji Astutik, 10.05.52.0021; Maryono, Maryono (Students Journal of Accounting and Banking, 2014)
This study aims to analyze the determinants of local government capital expenditure (Empirical Study on the District / City in Central Java period 2009 -2011). The sample used in this study were 35 districts / cities in Central Java, which is sourced from the Report of Actual Revenue and Expenditure Budget (budget) from 2009-2011. The data collection method used in this research is a method by taking the entire population census. The analytical tool used is multiple linear regression t test, f test, and test the coefficient of determination. The results of this study demonstrate that the General Allocation Fund (DAU) and the special allocation fund (DAK) noÂ significant effect on capital expenditures, while the partial local revenue (PAD) and the Brutto Regional Domestic Product (PDRB) significant effect on capital expenditures.Keywords: General Allocation Fund, Special Allocation Fund, Local Revenue, Brutto Regional Domestic Product, and Capital ExpenditureÂ